Second generation DNA-encoded dynamic combinatorial chemical libraries. Issue 26 (12th March 2019) - Reddavide, Francesco V.; Cui, Meiying; Lin, Weilin; Fu, Naiqiang; Heiden, Stephan; Andrade, Helena; Thompson, Michael; Zhang, Yixin
Abstract : A novel DNA-encoded chemical library architecture can mimic the mechanisms of immunity to evolve binders through recombination, dynamics and adaption. Abstract : We present a DNA-encoded chemical library, which allows dynamic selection followed by ligation of the encoding strands. As a chemical approach to mimic the genetic recombination process of adaptive immunity, the technology led to an enhanced enrichment factor and signal-to-noise ratio compared to static libraries.